TheValidity of Marriage Agreement Regarding Properties in Unregistered Marriages - Nurul Miqat; Muhammad Ikbal; Adfiyanti Fadjar; Ratu Ratna Korompol; Handar Subhandi Bakhtiar; Adiesty S.P. Syamsuddin (Yustisia, 2021)
The purpose of this study is to analyze the married couples engaged in an unregistered marriage and the position of the marriage agreement regarding the property as well as the concept of equal treatment of couples before and after isbat based on the theory of equality. This is important due to the legal gap observed in the norms, especially in relation to the unregistered legal marriages, despite the recognition of religious and registered marriages in Indonesian laws. This is legal research conducted using a conceptual and regulatory approach and the results defined an unregistered marriage as a legal marriage which fulfills the requirements determined by religion. Therefore, the failure to register a marriage does not invalidate its legality but there is a need for the record to be available with the state charged with such responsibility. Moreover, the agreements made concerning properties in unregistered marriages are valid as long as the parties conducted the process voluntarily and fulfill all the elements required. These agreements can also be recognized through the submission of isbat (marriage authorization) which recognizes and stipulates all activities conducted in the marriage before the isbat